Study on sealing performance of main gate valve of marine nuclear power plant based on fluid-solid-thermal coupling method - Yuqing, Chen; Hang, Yu; Shengwei, Fu; Ang, Li (Frontiers in Energy Research, 2024)
Introduction The main gate valve is a critical component of the coolant system in marine nuclear power plants, yet its integrity is often compromised by leakage, particularly during transient operations. This study employs a fluid-solid-thermal coupling method to numerically investigate the sealing performance of the main gate valve under rapid coolant temperature drops. Methods The analysis reveals that thermal shock-induced uneven stress and deformation significantly reduce contact pressure on the sealing surface, leading to leakage. Results and Discussion Notably, only when the bolt preload reaches the material yield limit can the valve maintain a seal during operation. Furthermore, the study demonstrates that a faster rate of coolant temperature drop exacerbates the leakage. These findings offer valuable insights for optimizing the operation of marine nuclear power plants and enhancing the structural integrity of the main gate valve.